Synthesis and Characterization of Fe(III) Complex with N'- (3-Nitrobenzoyl)Isonicotinohydrazide as an Anti-tuberculosis Candidate. (July 2019) - Ruswanto, R; Sarwatiningsih, Y; Pratita, ATK; Indra,; Dewi, R
Abstract: Recently, we have been conducted synthesis of complex compounds of Fe(III)N'-(3- nitrobenzoyl)isonicotinohydrazideusing refluxing N'-(3 -nitrobenzoyl)isonicotinohydrazideas ligands and FeCl3 .6H2 O as the metal at 75 °C for 6 hours in ethanol. The synthesis results obtained82.45% recovery, and from the purity test are shown with a narrow melting range is 220-222°C. Based on identification with UV-Visible spectrophotometer, infrared spectrometer and Atomic Absorption Spectrophotometer (AAS) indicate that the complex compound have λmax of 272.00 nm, giving vibration of Fe-O at 495.1 cm −1 and 599.6 cm −1 with formula complex compounds, namely [Fe(C13 H10 N4 O4 (H2 O)4 )Cl3 ].10 H2 O.